(3OjhGf GdeJfHis - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO GdcfOj GdeJfHj, CHh GdWjH,J (B254 (3g` s
(3ChdgG (B:s
(3bGd CHh GdWjH QMeg Gddg JYGdi jgfF GdCSJGP CHG GdeSc cGahQkG HGdOGQ GdLOjOI GdJi Ydi GdHQcI EfeG GdJgfFGJ GdCcaGA hdf jOfi ef GdHYOGA s
(3BNQgG (B:s
(3jfJgi HJQLeI dCHi GdWjH ai KdGK UaMGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QJH eYLeg Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B111 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B64s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B809s
Keywords: (3GdCOHs